Strategi Manajemen Stres Di Kalangan Perawat: Pengaruhnya Terhadap Produktivitas dan Kualitas Pelayanan - Muzakky, Ahmad; Ilmi, Muhamad Fadilah; Rostika, Reza; Nurazizah, Silvi; Safawi, Wafha Saleha; Ridwan , Heri; Saputra, Yudha Munajat; Sutresna, Iyos (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Stress management among nurses is an important strategy to improve mental and physical well-being in a demanding work environment. This study aims to explore the influence of stress management strategies on the productivity and quality of nursing services. The method used in this research is a literature review which includes an analysis of five recent studies on the effectiveness of stress management programs in hospitals. The research results showed that implementing stress management programs, such as stress coping and mindfulness training, significantly increased nurse productivity and service quality, as well as reduced the rate of medical errors and increased patient satisfaction. Keywords: Nursing, Productivity, Strategy, Stress Management.